ANALISIS STRATEGI PENGEMBANGAN KOMPETENSI PEGAWAI BERBASIS PEMBELAJARAN BERKELANJUTAN DI PT PLN (PERSERO) ULP LAKAWAN ENREKANG - Saifuddin, Saifuddin; Suparman, Suparman; Saidang, Saidang; AS, Arif Efendi; Haerusman, Haerusman (Komunitas Manajemen Kompetitif, 2025)
A sustainable employee competency development strategy is crucial for improving organizational performance, particularly in the public service sector, such as PT PLN (Persero). This research is motivated by the lack of a structured employee competency development system at the Lakawan Enrekang ULP as part of continuous learning. The purpose of this study was to analyze the implemented strategy and identify the forms of learning that develop in the workplace, both formal and informal. This research used a descriptive qualitative approach using in-depth interviews, observation, and documentation. The results indicate that formal training at the Lakawan ULP remains top-down and less relevant to actual employee needs. However, informal learning develops naturally through mentoring practices, technical discussions, and case reflections in the field. This learning has proven to be more adaptive and contextual, although it has not yet been institutionalized in the official HR development strategy. This research provides theoretical benefits in strengthening understanding of the importance of continuous learning in the workplace, and practical benefits as input for formulating locally context-based competency development policies at PT PLN (Persero).